Quercetin restores corticosteroid sensitivity in cells from patients with chronic obstructive pulmonary disease - Mitani, Akihisa (Exp Lung Res, 2017)
Corticosteroid resistance is a major barrier to the effective treatment of chronic obstructive pulmonary disease (COPD). Oxidative stress from cigarette smoke and chronic inflammation is likely to induce this corticosteroid insensitivity. Quercetin is a polyphenol that has been reported to be an active oxygen scavenger as well as a functional adenosine monophosphate-activated protein kinase (AMPK) activator. The aim of this study was to investigate the effect of quercetin on corticosteroid responsiveness in COPD cells. Corticosteroid sensitivity was examined in human monocytic U937 cells exposed to cigarette smoke extract (CSE) and peripheral blood mononuclear cells (PBMC) collected from patients with COPD. Corticosteroid sensitivity was determined as the dexamethasone concentration causing 40% inhibition of tumor necrosis factor alpha-induced CXCL8 production (Dex-IC(40)) in the presence or absence of quercetin. In U937 cells, treatment with quercetin activated AMPK and induced expression of nuclear factor erythroid 2-related factor 2, and consequently reversed CSE-induced corticosteroid insensitivity. PBMC from patients with COPD showed corticosteroid insensitivity compared with those from healthy volunteers, and treatment with quercetin restored corticosteroid sensitivity. In conclusion, quercetin restores corticosteroid sensitivity, and has the potential to be a novel treatment in combination with corticosteroids in COPD.